1991
DOI: 10.1288/00005537-199109000-00003
|View full text |Cite
|
Sign up to set email alerts
|

The intraoperative management of the thyroid gland during laryngectomy

Abstract: The standard of care of laryngeal cancer surgery is wide field excision of the larynx combined with ipsilateral thyroid lobectomy. A retrospective review of 247 laryngectomies performed between 1979 and 1989 was undertaken to determine specific intraoperative indications for thyroid gland removal. The incidence of thyroid disease in our patients with laryngeal cancer was compared to the normal population. Eight percent of thyroid specimens removed during laryngeal cancer surgery demonstrated invasion by squamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
78
0
7

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(90 citation statements)
references
References 36 publications
5
78
0
7
Order By: Relevance
“…In their study, Brennan and Dadas confirmed that routine thyroid gland removal during (pharyngo) laryngectomy is not indicated for the majority of (pharyngo) laryngeal cancers that do not meet the aforementioned criteria [5,6].…”
Section: Discussionmentioning
confidence: 90%
“…In their study, Brennan and Dadas confirmed that routine thyroid gland removal during (pharyngo) laryngectomy is not indicated for the majority of (pharyngo) laryngeal cancers that do not meet the aforementioned criteria [5,6].…”
Section: Discussionmentioning
confidence: 90%
“…However the incidence of thyroid involvement was noted to be around 10%. 3 This was noted, especially when anterior comissure, cricothyroid membrane was involved. Probably due to the stretching of collagen bundles by the tumour and creating direct pathway towards extralaryngeal space.…”
Section: Discussionmentioning
confidence: 99%
“…4 Similarly subglottic extension of more than 1cm and paraglottic extension also have been reported as a predictor for extralaryngeal spread and thyroid involvement. 3,[5][6][7][8][9] Subglottic extension more than 1.5 cm has been reported to have 100% chance of thyroid gland involvement as against 8% when its 0.5 cm into subglottis. 3,6 One of the main reasons for treatment failure has been attributed to, inadequate level 6 clearance in subglottic extension cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En effet, en période postopératoire, 10 à 25 % d'hypothyroïdie sont retrouvées chez des patients traités par radiothérapie seule. Ce chiffre atteint 45 % après chirurgie et radiothérapie et 70 % après chirurgie avec thyroïdectomie et radiothé-rapie complémentaire [3][4][5][6][7][8]. Concernant le métabolisme phosphocalcique, une hypoparathyroïdie postopératoire est retrouvée dans 25 % des cas après chirurgie et radiothérapie [9].…”
Section: Introductionunclassified